2003
DOI: 10.1159/000070043
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxygen Free Radical Scavengers in Acute Renal Failure Complicating Obstructive Jaundice

Abstract: Obstructive jaundice is associated with high morbidity and mortality. Major complications such as pulmonary dysfunction, renal failure and sepsis are frequently encountered. Recent studies and observations suggest that the free oxygen radicals (FORs) produced in obstructive jaundice may play a significant role in the etiopathogenesis of acute renal failure (ARF). Thirty rats were divided into three groups, as sham, control and treatment groups containing 10 rats each. Laparatomy was performed on each animal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
13
1
1
Order By: Relevance
“…We observed a significant decrease in pulmonary neutrophil leukocyte infiltration in the treatment group in comparison to the control group (p<0.05). Although the etiology of renal function disorders in obstructive jaundice is yet to be known, it has been suggested that cellular and extracellular hypovolemia, increase in oxygen free radicals, and decrease in antioxidant functions play a significant role (26,27). While there was a decrease in the scope of renal tubule damage in the treatment group of our study, it was not statistically significant.…”
Section: Discussioncontrasting
confidence: 62%
“…We observed a significant decrease in pulmonary neutrophil leukocyte infiltration in the treatment group in comparison to the control group (p<0.05). Although the etiology of renal function disorders in obstructive jaundice is yet to be known, it has been suggested that cellular and extracellular hypovolemia, increase in oxygen free radicals, and decrease in antioxidant functions play a significant role (26,27). While there was a decrease in the scope of renal tubule damage in the treatment group of our study, it was not statistically significant.…”
Section: Discussioncontrasting
confidence: 62%
“…The depletion of the extracellular compartment (4), myocardial dysfunction, and altered hemodynamic status (5) have been linked to renal failure in biliary obstruction. In addition, severe oxidative stress has been implicated in the renal dysfunction associated to experimental OJ (6,7) as well as other liver diseases (8). Other lines of research have looked at the involvement of vasoactive mediators such as endothelin-1 (ET-1).…”
Section: Introductionmentioning
confidence: 99%
“…Renal failure is one of the most frequent complications of obstructive jaundice and acute renal failure is observed in 4-18% of the patients (Kucuk et al 2003). Similarly, acute renal injury secondary to intra or extrahepatic bile duct obstruction is one of the main causes of postoperative multiple system failure, which affects approximately 6%-8% of patients with over 68% mortality (Fogarty et al 1995;Holt et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This can be related to significant biochemical and metabolic changes that mightplay an independent role in contributing to the development of renal failure. These biochemical alterations include accumulation of bile acids and billirubin, increased levels of free oxygen radicals, endogenous opioids, and endotoxemia (Green and Better 1995;Kucuk et al 2003). The role of bile constituents (e.g., bile acids, bilirubin, cholesterol) is still controversial in mediating renal damage, but the role of plasma endogenous opioids, mainly methionine enkephalin, is extensively investigated and confirmed in terms of the pathophysiology of cholestatic disease and its complications (Dehpour et al 1998;Ghaffari et al 2004;Swain et al 1992).…”
Section: Introductionmentioning
confidence: 99%